Room-temperature vulcanized silicone sealant for yellowing-resistant bulb lamp and preparation method of room-temperature vulcanized silicone sealant
By using RTV-1 silicone sealant and high-yield zirconium-based catalyst in the sealant of LED bulb lamp, the problems of yellowing, corrosion and cracking of PC bubble shells are solved, and the advantages of silicone sealant are achieved Yellowing resistance, corrosion resistance and simplified glue application process.
Patent Information
- Application Number
- CN202510067642.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-02-18
AI Technical Summary
In the use of the sealant of LED bulb lamps, there are problems such as yellowing of the PC bulb shell, corrosion cracking, blackening of the surface of the lamp beads, falling luminous flux, drifting of color temperature and complex glue application process.
Using RTV-1 silicone sealant, through the use of high yield zirconium catalysts, specific polydimethylsiloxanes, stearic acid modified active nanocalcium carbonate, hydrophobic pyrolyzed silica and activated heavy calcium carbonate Silicone sealant with excellent yellowing and corrosion resistance is prepared.
It significantly improves the yellowing and corrosion resistance of silicone sealant, meets the use requirements of LED lamps (especially bulb lamps), simplifies the glue application process, and improves the mechanical properties and adhesion of the product.
Smart Images

Figure CN119463802A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a room temperature vulcanized silicone sealant for yellowing resistant bulb lamps and a preparation method thereof. Background Art
[0002] Ultra-bright light-emitting diodes (LEDs) have the advantages of high efficiency, energy saving, small size, and long life. The electricity they consume is only 1 / 10 of that of traditional incandescent lamps. They are widely used in lighting, landscape lighting, automobiles, communications, and multimedia electronic product lamps. LED lamps, especially LED light source products, such as bulbs, parabolic aluminum-plated reflector lamps (PAR lamps for short), bromine tungsten lamps (BR lamps for short), etc., require adhesives for bonding during assembly. For example, between the bulb shell and the lamp body, and between the LED light source board and the radiator, they all need to be fixed with the help of adhesives. Silicone materials are resistant to high and low temperatures, weather aging, and have excellent electrical properties. They are widely used in the LED bonding and sealing industry; the silicone adhesives used for sealing LED bulbs are mainly RTV-1 (single-component room temperature vulcanized silicone rubber), RTV-2 (two-component room temperature vulcanized silicone rubber), etc. RTV-1 mainly includes Nanda deethanol type, deacetone type, and titanate demethanol type products; due to the differences in raw materials and production processes, different silicone adhesives will cause yellowing, cracking, and shedding of the bulb shell (such as PC material) to varying degrees after being used for LED packaging. RTV-2 mainly includes organic tin dealcohol products, such as DOWSIL EA3500G, in which the volume ratio of components A and B is 10:1; this product uses restricted organic tin compounds, which to a certain extent affects its environmental performance. At the same time, the mixing ratio of A and B in this product is too disparate, which requires high precision of the glue application equipment, is expensive, and has a large size, which is not conducive to implementation. At the same time, in order to enhance the bonding effect, the existing technology attempts to add excessive amounts of primary amino silane, which can also cause problems such as yellowing and cracking of the PC bulb shell.
[0003] As LED lamps and lamps occupy an increasing share in the general lighting market, silicone sealants must match the production process needs of increasing production capacity. The current mainstream production process is to immediately put on the bulb shell after applying glue on the lamp body, and then transfer the sealed bulb into the lighting aging furnace (105℃) for 30 minutes of aging, rather than waiting for the glue to cure well at room temperature before lighting aging. Although RTV-2 silicone sealant has the ability to cure quickly to meet the production process requirements, its ability to prevent A and B ratio deviation is poor and the equipment cost is too high. At present, the equipment is mainly used in industries with high added value such as automotive lamps, and its application range is relatively limited. At the same time, in order to improve bonding and increase catalytic reaction activity, a lot of primary amino silanes are added to RTV-2 silicone sealant. Primary amino silanes may react with certain components in PC materials, which can easily cause PC corrosion and yellowing, affecting the use of parts.
[0004] Chinese patent application CN118085808A discloses a high temperature resistant silicone rubber and its preparation method, wherein the silicone rubber is prepared by the synergistic use of N-halamine modified polysiloxane, zirconium modified polysiloxane and vinyl silicone oil to improve the high temperature resistance of the silicone rubber. Chinese patent CN102516772B discloses a dealcoholized single component room temperature vulcanized silicone rubber and its preparation method, wherein a, ω-dihydroxy polydimethylsiloxane is used as the base rubber, supplemented with linear polydimethylsiloxane, and an organic titanate integral compound is used as a catalyst to obtain a silicone rubber with low viscosity, solvent-free, high flow and fast curing characteristics.
[0005] However, these existing technologies have not solved the above technical problems. In this context, the LED lighting industry is in urgent need of silicone sealants with no yellowing, corrosion and cracking of PC bulbs, no blackening of the lamp bead surface, no luminous flux reduction, no color temperature drift, and simple gluing process. Summary of the invention
[0006] RTV-1 zirconate system outsoles generally use secondary amine crosslinkers, otherwise there will be coexistence problems with zirconate catalysts, resulting in poor storage stability; it just provides a basis for solving PC yellowing and corrosion. The present invention aims at the problems of PC corrosion and yellowing that are prone to occur during the use of existing organic silicone sealants, and provides an RTV-1 type silicone sealant with good performance and easy production and construction.
[0007] The first aspect of the present invention provides a room temperature vulcanized silicone sealant for yellowing resistant bulb lamps. The raw materials for preparing the silicone sealant include, by weight: 80-120 parts of polydimethylsiloxane; 1-5 parts of catalyst; Filling particles 100-130 parts; 2-10 parts of cross-linking agent; 0.5-2 parts of tackifier; Lubricant 5-20 parts.
[0008] In some preferred embodiments, the polydimethylsiloxane includes a combination of one or more of hydroxyl-terminated polydimethylsiloxane and trimethoxysilyl-terminated polydimethylsiloxane.
[0009] In some preferred embodiments, the viscosity of the polydimethylsiloxane is 1500-25000 cst, which can be exemplified as 1500 cst, 5000 cst, 10000 cst, 20000 cst, and 25000 cst.
[0010] The study found that the higher the viscosity of polydimethylsiloxane and the longer the distance between the crosslinking points, the greater the elongation at break and the peel strength of the prepared silicone sealant. In addition, the higher the viscosity, the lower the extrusion of the silicone sealant and the poorer the construction performance; the lower the viscosity, the shorter the distance between the crosslinking points, the higher the hardness of the prepared silicone sealant, the lower the elongation at break, and the worse the mechanical properties. At the same time, the silicone sealant obtained has strong operability, high extrusion performance, and high gluing efficiency. In order to make the sealant have good mechanical properties and gluing operation performance, high and low viscosity polydimethylsiloxanes can be used in combination.
[0011] Further preferably, the polydimethylsiloxane is a compound of polydimethylsiloxane with a viscosity of 20000 cst and polydimethylsiloxane with a viscosity of 1500 cst, and the mass ratio of the two is (2-8):1.
[0012] In some preferred embodiments, the raw materials for preparing the catalyst include: zirconium n-propoxide, acyl ester ligands and alcohol solvents.
[0013] In some preferred embodiments, the acyl ester ligand includes at least one of ethyl acetoacetate, methyl pivaloyl acetate, and ethyl trifluoroacetoacetate.
[0014] In some preferred embodiments, the catalyst is at least one of diisopropoxybis(ethyl acetoacetate) zirconium, diisopropoxybis(methyl pivaloyl acetate) zirconium, and diisopropoxybis(ethyl trifluoroacetoacetate) zirconium.
[0015] The alcohol solvent may be methanol, ethanol, propanol or butanol.
[0016] In some preferred embodiments, the alcohol solvent is n-propanol.
[0017] In some preferred embodiments, the mass ratio of the zirconium n-propoxide to the acyl ester ligand is 50:(20-40).
[0018] In some preferred embodiments, the catalyst preparation step comprises: mixing zirconium n-propoxide and an alcohol solvent, and adding an acyl ester ligand dropwise under stirring; after the addition is completed, stirring and reacting at room temperature for 20-30 hours, and purifying to obtain a catalyst product.
[0019] The present invention removes alcohol solvent byproducts in the reaction system through purification, and the purification can be carried out by rotary evaporation and the like.
[0020] The catalyst prepared by the present invention is prepared by ligand exchange reaction of zirconium n-propoxide and specific acyl ester ligands in alcohol solvents to obtain a high-yield zirconium catalyst. The obtained catalyst is added to silicone sealant to significantly improve the yellowing resistance and corrosion resistance of silicone sealant, and can meet the use requirements of LED lamps (especially bulbs). It is speculated that ethyl acetoacetate, methyl pivaloyl acetate, and ethyl trifluoroacetoacetate have high coordination activity in n-propanol and can effectively combine with zirconium atoms to form a double coordination complex. The complex is added to silicone sealant as a catalyst, has good formula stability, will not trigger adverse reactions with raw materials such as cross-linking agents, thereby maintaining stable chemical properties, and giving silicone sealant yellowing resistance, corrosion cracking resistance and other properties.
[0021] In some preferred embodiments, the filling particles include at least one of inorganic reinforcing fillers or extending fillers such as nano calcium carbonate, pyrogenic silica, precipitated silica, and heavy calcium carbonate.
[0022] Both pyrogenic silica and precipitated silica are excellent inorganic reinforcing fillers with a specific surface area of at least 100m 2 / g; It was found that when the specific surface area of the filler is too small, the reinforcement effect is not obvious, and when the specific surface area is too large, the thickening effect is obvious, which reduces the extrudability of the material. The present invention preferably performs silane hydrophobic surface treatment on the inorganic filler to improve the reinforcement and peel strength. At the same time, nano-silicon dioxide has a relatively large specific surface area and a chemical structure similar to polysiloxane, and has obvious interaction force. The effect of reducing extrudability while reinforcing is significantly better than nano-calcium carbonate and heavy calcium carbonate; it is further preferred that the addition amount is 5 to 25 parts.
[0023] Nano calcium carbonate is a good reinforcing filler for silicone sealant. It is preferred to perform fatty acid surface hydrophobic modification on nano calcium carbonate to increase the good adhesion and moisture and heat aging resistance of silicone sealant cured product. The particle size of the nano calcium carbonate is 40-80nm; it can be listed as 40nm, 45nm, 50nm, 55nm, 56nm, 57nm, 58nm, 59nm, 60nm, 61nm, 62nm, 63nm, 64nm, 65nm, 70nm, 75nm, 80nm; the most preferred is 60nm. If the particle size is too small, the surface interaction is obvious, which reduces the extrudability of the silicone sealant composition; if the particle size is too large, the reinforcing effect will be lost and the adhesion will be reduced.
[0024] Heavy calcium carbonate is a good filler for silicone sealant. It is preferred to perform surface hydrophobic modification on heavy calcium carbonate to improve its dispersion and reinforcement effect. If the surface hydrophobic modification is not performed, the adhesiveness and resistance to moisture and heat aging of the adhesive will be reduced. At the same time, active heavy calcium carbonate can work together with active nano calcium carbonate to effectively improve the extrudability of the material. Preferably, the particle size of the heavy calcium carbonate is 0.01~0.1um, and the addition amount is 10~30 parts; when the addition amount is too much, the tensile strength of the adhesive decreases.
[0025] Preferably, in order to prevent structuring and improve reinforcement, the filling particles may be subjected to silanization hydrophobic surface modification to obtain hydrophobic silica.
[0026] Preferably, the mass ratio of the nano calcium carbonate, hydrophobic silicon dioxide and heavy calcium carbonate is 100:5~25:10~30.
[0027] The lubricant can be exemplified by trimethylsilyl-terminated polydimethylsiloxane having trimethylsilyl at one end and trimethoxysilyl at the other end, single-end alkoxy silicone oil, alkyl silicone oil, silicone masterbatch, and the like.
[0028] In some preferred embodiments, the lubricant is an alkyl silicone oil; more preferably, it is a long-chain alkyl silicone oil.
[0029] Preferably, the viscosity of the lubricant is 250-500 cst, which can be 250 cst, 260 cst, 270 cst, 280 cst, 290 cst, 300 cst, 310 cst, 320 cst, 330 cst, 340 cst, 350 cst, 360 cst, 370 cst, 380 cst, 390 cst, 400 cst, 450 cst, 500 cst, and more preferably 300-400 cst. The present invention preferably uses long-chain alkyl silicone oil, which has a higher filler filling capacity than other lubricants and is more conducive to improving the extrudability of the silicone sealant composition.
[0030] The crosslinking agent may be exemplified by a combination of one or more of methyltrimethoxysilane, vinyltrimethoxysilane, methyltrimethoxysilane oligomer, vinyltrimethoxysilane oligomer, dimethyldimethoxysilane, diphenyldimethoxysilane, and methylphenyldimethoxysilane.
[0031] Preferably, the adhesion promoter includes one or more combinations of (meth)acrylsilane, epoxysilane, secondary aminosilane, aminosilane oligomer, mercaptosilane and isocyanatesilane.
[0032] The adhesion promoter can be exemplified by a combination of one or more of aminosilane oligomers, γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, 2,3-epoxypropyltrimethoxysilane, acetyltrimethoxysilane, γ-(methacryloyloxy)propyltrimethoxysilane, γ-glycidyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-mercaptopropylethoxysilane.
[0033] More preferably, the crosslinking agent includes one or more combinations of methyltrimethoxysilane, vinyltrimethoxysilane, methyltrimethoxysilane oligomer, and vinyltrimethoxysilane oligomer.
[0034] More preferably, the adhesion promoter includes a ring-opening addition oligomer of KH560 and KH550, an aminosilane oligomer, such as Dynasylan® 1146.
[0035] Further preferably, the mass ratio of the cross-linking agent to the tackifier is (3-5):1.
[0036] The present invention can also add functional additives according to actual needs, such as flame retardants, thermal conductors, antioxidants, ultraviolet absorbers, etc.; there is no special requirement for the type and amount of the added functional additives, as long as the functional purpose can be achieved.
[0037] The second aspect of the present invention provides a method for preparing a room temperature vulcanized silicone sealant for a yellowing resistant bulb lamp, the preparation steps of the silicone sealant comprising: Mix polydimethylsiloxane and filler particles, stir for 1-3 hours under negative pressure at 100-140°C; cool to below 45°C, add lubricant, crosslinking agent and tackifier, and stir evenly; add catalyst, evacuate and stir evenly to obtain silicone sealant product, and seal for later use.
[0038] Beneficial effects: The present invention provides a room temperature vulcanized silicone sealant for yellowing resistant bulb lamps and a preparation method thereof, which has the following advantages: (1) The catalyst prepared by the present invention is a high-yield zirconium catalyst prepared by a ligand exchange reaction between zirconium n-propoxide and acyl ester ligands in an alcohol solvent. The obtained catalyst is added to silicone sealant to significantly improve the yellowing resistance and corrosion resistance of the silicone sealant, and can meet the use requirements of LED lamps (especially bulb lamps).
[0039] (2) The preferred acyl ester ligands of the present invention are ethyl acetoacetate, methyl pivaloyl acetate, and ethyl trifluoroacetoacetate, that is, the obtained catalysts are diisopropoxybis(ethyl acetoacetate) zirconium, diisopropoxybis(methyl pivaloyl acetate) zirconium, and diisopropoxybis(trifluoroacetoacetate) zirconium. The obtained silicone sealant can coexist with the crosslinking agent, has good formula compatibility, and significantly improves the storage stability of the silicone sealant.
[0040] (3) The present invention preferably uses a specific polydimethylsiloxane, combined with 40-80nm stearic acid-modified active nano calcium carbonate and a specific surface area of 150m 2 / g hydrophobic silica (fumed silica), 0.01-0.1um active heavy calcium carbonate and long-chain alkyl silicone oil with a viscosity of 250-500cst are added with a zirconium-based catalyst to produce a silicone sealant; the sealant can be vulcanized at room temperature, and the vulcanized sealant has good mechanical properties and strong adhesion to PC, metals, etc.; it can be well used in the processing of bulbs, etc.
[0041] (4) The raw materials of the present invention are easily available and the preparation method is simple. When in use, the sealant is applied to the surface of the lamp body, and after the bulb shell is buckled, the colloid can be cured and the lamp is aged simultaneously; the operation is convenient and the practicability is strong.
[0042] (5) Compared with conventional titanate catalysts and other products, the present invention has excellent yellowing resistance, cracking resistance and corrosion resistance, and can effectively solve the technical problems such as yellowing, corrosion cracking, blackening of the lamp bead surface, reduced luminous flux, color temperature drift, and complex sizing process that are prone to occur during the processing of existing PC bulbs. It has superior technical improvement significance and is suitable for market promotion. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 . A physical picture of the silicone sealant provided in Example 1 after yellowing test; Figure 2 . A physical picture of the silicone sealant provided in Example 2 after yellowing test; Figure 3 . A physical picture of the silicone sealant provided in Example 3 after yellowing test; Figure 4 . A physical picture of the silicone sealant provided in Example 4 after yellowing test; Figure 5 . A physical picture of the silicone sealant provided in Example 5 after yellowing test; Figure 6 Comparative Example 1 provides a physical picture of the silicone sealant after yellowing test; Figure 7 . Actual picture of the silicone sealant provided in Comparative Example 2 after yellowing test. DETAILED DESCRIPTION
[0044] The information of some raw materials used in the examples and comparative examples of the present invention is as follows: Hydroxy-terminated polydimethylsiloxane: viscosity is 20000cst (test temperature 25℃), sourced from Shandong Dongyue Company.
[0045] Hydroxy-terminated polydimethylsiloxane: viscosity is 1500cst (test temperature 25°C), sourced from Shandong Dongyue Company.
[0046] Trimethoxysilyl-terminated polydimethylsiloxane: viscosity is 1500cst (test temperature 25°C), sourced from Guangzhou Chengtian New Materials Co., Ltd.
[0047] Trimethoxysilyl-terminated polydimethylsiloxane: viscosity is 20000cst (test temperature 25°C), sourced from Jiangsu Kexing New Materials Co., Ltd.
[0048] Stearic acid modified active nano calcium carbonate: particle size is 60nm; sourced from Guangxi Warner Co., Ltd.
[0049] Hydrophobic pyrogenic silica: surface area 150m 2 / g; derived from Cabot.
[0050] Active heavy calcium carbonate: particle size is 0.01~0.1μm; sourced from Lida Superfine Industry (Suzhou) Co., Ltd.
[0051] Long-chain alkyl silicone oil: viscosity is 350cst (test temperature 25°C); sourced from Shandong Dayi Chemical Co., Ltd.
[0052] The crosslinking agent is methyltrimethoxysilane.
[0053] The tackifier is aminosilane oligomer: it comes from Guangzhou Jianyi Chemical Import and Export Co., Ltd., and its model is Dynasylan®1146.
[0054] The zirconium n-propoxide solution was obtained from Merck, wherein the concentration of zirconium n-propoxide was 70 wt % and the solvent was n-propanol.
[0055] Note: Unless otherwise specified, the raw materials used in the present invention are all commercially available; the room temperature is 25°C.
[0056] Example Example 1 The present embodiment provides a room temperature vulcanized silicone sealant for yellowing resistant bulb lamps and a preparation method thereof.
[0057] In parts by weight, the raw materials for preparing the silicone sealant include: 100 parts of polydimethylsiloxane, 2.5 parts of catalyst, 115 parts of filling particles, 5.5 parts of cross-linking agent, 1.2 parts of tackifier, and 10 parts of lubricant.
[0058] The raw materials for preparing the catalyst include: zirconium n-propoxide and acyl ester ligand (ethyl acetoacetate).
[0059] The preparation steps of the catalyst include: placing 50g of zirconium n-propoxide solution in a 100ml three-necked flask, and dripping 27.81g of ethyl acetoacetate under stirring (dripping is completed in 30 minutes); after the dripping is completed, stirring and reacting at room temperature for 24 hours, and removing the byproduct n-propanol by rotary evaporation to obtain 49g of catalyst product; the obtained catalyst product is mainly diisopropoxy bis(ethyl acetoacetate) zirconium.
[0060] The polydimethylsiloxane is hydroxyl-terminated polydimethylsiloxane with a viscosity of 20000 cst.
[0061] The filling particles are active nano calcium carbonate modified by stearic acid, and the particle size is 60nm.
[0062] The preparation steps of the silicone sealant include: mixing hydroxyl-terminated polydimethylsiloxane and filler particles in a planetary agitator, vacuuming and stirring for 2 hours at 130° C. and a vacuum degree of -0.098 MPa; cooling to 35° C., adding a lubricant, a cross-linking agent and a tackifier, and stirring for 30 minutes in a moisture-proof condition; adding a catalyst, vacuuming and stirring for 60 minutes to obtain a silicone sealant product, and sealing for later use.
[0063] Example 2 The present embodiment provides a room temperature vulcanized silicone sealant for yellowing resistant bulb lamps and a preparation method thereof.
[0064] In parts by weight, the raw materials for preparing the silicone sealant include: 100 parts of polydimethylsiloxane, 2.3 parts of catalyst, 115 parts of filling particles, 5.5 parts of cross-linking agent, 1.2 parts of tackifier, and 10 parts of lubricant.
[0065] The raw materials for preparing the catalyst include: zirconium n-propoxide solution and acyl ester ligand (methyl pivaloyl acetate).
[0066] The preparation steps of the catalyst include: placing 50g of zirconium n-propoxide solution in a 100ml three-necked flask, and dripping 33.8g of methyl pivaloyl acetate under stirring (dripping is completed in 30 minutes); after the dripping is completed, stirring and reacting at room temperature for 24 hours, and removing the byproduct n-propanol by rotary evaporation to obtain 54g of catalyst product; the obtained catalyst product is mainly diisopropoxy bis(methyl pivaloyl acetate) zirconium.
[0067] The polydimethylsiloxane is trimethoxysilyl-terminated polydimethylsiloxane with a viscosity of 20,000 cst.
[0068] The filling particles are active nano calcium carbonate modified by stearic acid, and the particle size is 60nm.
[0069] The preparation steps of the silicone sealant include: mixing trimethoxysilyl-terminated polydimethylsiloxane and filler particles in a planetary stirrer, vacuuming and stirring for 2 hours at 130° C. and a vacuum degree of -0.098 MPa; cooling to 35° C., adding a lubricant, a cross-linking agent and a tackifier, and stirring for 30 minutes under moisture-proof conditions; adding a catalyst, vacuuming and stirring for 60 minutes to obtain a silicone sealant product, and sealing for later use.
[0070] Example 3 The present embodiment provides a room temperature vulcanized silicone sealant for yellowing resistant bulb lamps and a preparation method thereof.
[0071] The raw materials for preparing the silicone sealant include, by weight: 100 parts of trimethoxysilyl-terminated polydimethylsiloxane, 2.3 parts of catalyst, 115 parts of filling particles, 5.5 parts of cross-linking agent, 1.2 parts of tackifier, and 10 parts of lubricant.
[0072] The raw materials for preparing the catalyst include: zirconium n-propoxide and acyl ester ligand (ethyl trifluoroacetoacetate).
[0073] The preparation steps of the catalyst include: placing 50g of zirconium n-propoxide solution in a 100ml three-necked flask, and dripping 39.34g of ethyl trifluoroacetoacetate under stirring (dripping is completed in 30 minutes); after the dripping is completed, stirring and reacting at room temperature for 24 hours, and removing the byproduct n-propanol by rotary evaporation to obtain 59g of catalyst product; the obtained catalyst product is mainly diisopropoxybis(ethyl trifluoroacetoacetate) zirconium.
[0074] The polydimethylsiloxane is a compound of trimethoxysilyl-terminated polydimethylsiloxane (viscosity 20000 cst) and trimethoxysilyl-terminated polydimethylsiloxane (viscosity 1500 cst), with a mass ratio of 2:1.
[0075] The filling particles are active nano calcium carbonate modified by stearic acid, and the particle size is 60nm.
[0076] The preparation steps of the silicone sealant include: mixing trimethoxysilyl-terminated polydimethylsiloxane and filler particles in a planetary stirrer, vacuuming and stirring for 2 hours at 130° C. and a vacuum degree of -0.098 MPa; cooling to 35° C., adding a lubricant, a cross-linking agent and a tackifier, and stirring for 30 minutes under moisture-proof conditions; adding a catalyst, vacuuming and stirring for 60 minutes to obtain a silicone sealant product, and sealing for later use.
[0077] Example 4 This embodiment provides a room temperature vulcanized silicone sealant for yellowing resistant bulb lamp and a preparation method thereof, and the specific implementation method is the same as that of embodiment 1; the difference is that: The polydimethylsiloxane is a compound of hydroxyl-terminated polydimethylsiloxane (viscosity 20000 cst) and hydroxyl-terminated polydimethylsiloxane (viscosity 1500 cst), and the mass ratio of the two is 3:1.
[0078] Example 5 This embodiment provides a room temperature vulcanized silicone sealant for yellowing resistant bulb lamp and a preparation method thereof, and the specific implementation method is the same as that of embodiment 1; the difference is that: The filling particles are a mixture of stearic acid-modified active nano calcium carbonate, hydrophobic pyrolyzed silicon dioxide and active heavy calcium carbonate, with a mass ratio of 85:10:20.
[0079] Comparative Example 1 This comparative example provides a room temperature vulcanized silicone sealant for yellowing resistant bulb lamps and a preparation method thereof. The specific implementation method is the same as that of Example 1; the difference is that the catalyst is replaced by a titanate catalyst, specifically Tyzor® 726, which is derived from Dovkaite.
[0080] Comparative Example 2 This comparative example provides a room temperature vulcanized silicone sealant for yellowing resistant bulb lamps and a preparation method thereof. The specific implementation method is the same as that of Example 2; the difference is that the catalyst is replaced by a titanate catalyst, specifically Tyzor® 9000, which is derived from Dovkaite.
[0081] Performance Testing Methods The silicone sealants obtained in Examples 1-3 and Comparative Examples 1-2 were subjected to the following tests. The test results are shown in Table 1.
[0082] 1) Surface drying time test: Refer to GB / T 13477.5-2002 method, at 25℃, 55RH%, apply glue on white paper, touch the silicone with your hand, if it is not sticky, it is the surface drying time of the silicone.
[0083] 2) Sheet physical property test: The silicone sealant was injected into a 0.2 mm thick mold and vulcanized for 7 days at 25°C and 55 RH% to make dumbbell specimens. The tensile strength and elongation at break of the test samples were tested according to GB / T 528-2009.
[0084] 3) Shear test: The silicone sealant was used for PC-PC and aluminum-aluminum sandwich bonding, with a layer thickness of 0.2 mm. The samples were prepared with reference to GB / T7124-2008, and vulcanized for 7 days at 25°C and 55RH%, and the shear strength of the samples was tested.
[0085] 4) Hardness test: With reference to GB / T 531.1-2008, inject silicone sealant into the mold, vulcanize for 7 days at 25℃ and 55RH%, and test the hardness of the sample.
[0086] 5) Yellowing test: Take 11g of silicone sealant and evenly apply it on the inner wall of the PC bubble shell (the thickness of the glue layer is 3mm), then place the glue-coated PC bubble shell with the open end facing down on a clean glass plate, and apply the same glue at the connection between the PC bubble shell and the glass plate to make the PC bubble shell in a relatively sealed state, then immediately put the sealed PC bubble shell into a 105℃ oven and bake it for 24 hours. After taking it out and cooling it, observe the yellowing and corrosion of the inner wall of the PC bubble shell.
[0087] 6) Torque test: Apply silicone sealant to the edge opening of the PC bulb shell, and then seal the bulb shell on the open end of the lamp body. Curing at room temperature for 24 hours, test the torque, and the torque is required to be ≥3.5Nm.
[0088] 7) Storage test: The silicone sealant was sealed in an aluminum toothpaste tube and placed in a 70°C oven for 7 days, cooled to room temperature, and the surface drying time was tested at 25°C and 55RH%.
[0089] 8) Extrusion test: The pneumatic extrusion tester is used to simulate the glue discharging test of the three-axis glue coating machine. The glue discharging weight is tested under the test conditions of 5 seconds and 75psi.
[0090] Table 1
[0091] From the data in Table 1 and Figures 1 to 7It can be seen that the present invention adds a homemade zirconium catalyst when preparing silicone sealant, and uses it together with specific polydimethylsiloxane, filler particles, cross-linking agent and tackifier, and the resulting silicone sealant has excellent anti-yellowing and corrosion resistance effects. And by compounding high and low viscosity polydimethylsiloxanes, as well as stearic acid-modified active nano-calcium carbonate, hydrophobic pyrolytic silica, and active heavy calcium carbonate, the extrudability of silicone sealant can be improved, and the product glue efficiency is improved. However, comparative examples 1-2 use titanate catalysts, and the silicone sealant finally obtained has obvious yellowing and cracking phenomena, which cannot meet the use requirements of LED lamps. And after comparative example 2 was stored at 70°C for 7 days, the cross-linking agent was consumed to a certain extent, resulting in a significant extension of the surface drying time of the silicone sealant.
Claims
1. A room temperature vulcanized silicone sealant for yellowing resistant bulb lamp, characterized in that: In parts by weight, the raw materials for preparing the silicone sealant include: 80-120 parts of polydimethylsiloxane; 1-5 parts of catalyst; Filling particles 100-130 parts; 2-10 parts of cross-linking agent; 0.5-2 parts of tackifier; Lubricant 5-20 parts; The raw materials for preparing the catalyst include: zirconium n-propoxide, acyl ester ligands and alcohol solvents; The acyl ester ligand includes at least one of ethyl acetoacetate, methyl pivaloyl acetate, and ethyl trifluoroacetoacetate.
2. The room temperature vulcanized silicone sealant for yellowing resistant bulb lamp according to claim 1, characterized in that: The preparation steps of the catalyst include: mixing zirconium n-propoxide and an alcohol solvent, and adding an acyl ester ligand dropwise under stirring; after the addition is completed, stirring at room temperature for 20-30 hours, and purifying to obtain a catalyst product; The alcohol solvent is n-propanol; The mass ratio of the zirconium n-propoxide to the acyl ester ligand is 50:(20-40).
3. The room temperature vulcanized silicone sealant for yellowing resistant bulb lamp according to claim 1, characterized in that: The polydimethylsiloxane includes a combination of one or more of hydroxyl-terminated polydimethylsiloxane and trimethoxysilyl-terminated polydimethylsiloxane.
4. The room temperature vulcanized silicone sealant for yellowing resistant bulb lamp according to claim 3, characterized in that: The viscosity of the polydimethylsiloxane is 1500-25000 cst, and the test temperature is 25°C.
5. The room temperature vulcanized silicone sealant for yellowing resistant bulb lamp according to claim 1, characterized in that: The filling particles include one or more of nano calcium carbonate, pyrogenic silica, precipitated silica, and heavy calcium carbonate.
6. The room temperature vulcanized silicone sealant for yellowing resistant bulb lamp according to claim 5, characterized in that: The nano calcium carbonate is surface treated with fatty acid, and the particle size of the nano calcium carbonate after the surface treatment with fatty acid is 40-80nm.
7. The room temperature vulcanized silicone sealant for yellowing resistant bulb lamp according to claim 1, characterized in that: The crosslinking agent includes one or more of methyltrimethoxysilane, vinyltrimethoxysilane, methyltrimethoxysilane oligomer, vinyltrimethoxysilane oligomer, dimethyldimethoxysilane, diphenyldimethoxysilane, and methylphenyldimethoxysilane.
8. The room temperature vulcanized silicone sealant for yellowing resistant bulb lamp according to claim 1, characterized in that: The adhesion promoter includes one or more combinations of (meth)acrylsilane, epoxysilane, secondary aminosilane, aminosilane oligomer, mercaptosilane and isocyanatesilane.
9. The room temperature vulcanized silicone sealant for yellowing resistant bulb lamp according to claim 1, characterized in that: The lubricant includes at least one of dimethyl silicone oil, single-end alkoxy silicone oil, and long-chain alkyl silicone oil; The viscosity of the lubricant is 250~500cst.
10. A method for preparing the room temperature vulcanized silicone sealant for yellowing resistant bulb lamps according to any one of claims 1 to 9, characterized in that: The preparation steps of the silicone sealant include: Mix polydimethylsiloxane and filler particles, stir for 1-3 hours under negative pressure at 100-140°C; cool to below 45°C, add lubricant, crosslinking agent and tackifier, and stir evenly; add catalyst, evacuate and stir evenly to obtain silicone sealant product, and seal for later use.
Citation Information
Patent Citations
Dealcoholized one-component room temperature vulcanized silicone rubber and preparation method thereof
CN102516772B
High-temperature-resistant silicone adhesive and preparation method thereof
CN118085808A
Thermally conductive silicone compositions and methods of producing interstitial fillers using same
CN118251465A
Organosiloxane compositions
CN1394221A
Heat curable resin composition and semiconductor sealing material
JP2013209560A